Exploring the potential and limits of a neuroscientific approach to entrepreneurship. (September 2019) - Nicolaou, Nicos; Lockett, Andy; Ucbasaran, Deniz; Rees, Geraint
We critically examine the potential that neuroscience holds for the future of entrepreneurship research and provide a framework for entrepreneurship researchers interested in pursuing this line of inquiry. Specifically, we propose four complementary mechanisms through which neuroscience can inform entrepreneurship theory and research. We conclude with a discussion of the limitations and ethical implications of a neuroscientific approach to entrepreneurship.